Theory of Planned Behaviour Pada Niat Pembayaran Zakat, Infak, Sedekah (ZIS) Secara Online - Alexandra, Kanaya; Puspawati, Dewita (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the factors influencing people's intention to make Zakat, Infak, and Sedekah (ZIS) payments online using the Theory of Planned Behavior (TPB) approach. This model examines the influence of attitude, subjective norms, perceived behavioral control, and trust on the intention to make digital ZIS payments. The study employs a quantitative method using a survey technique involving 105 student respondents in Surakarta. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that attitude and subjective norms significantly influence the intention to pay ZIS online. Conversely, perceived behavioral control and trust do not have a significant impact on this intention. These findings indicate that individual beliefs and social influence play a more dominant role in driving digital ZIS payments compared to perceived behavioral control and trust in the payment system. The implications of this study highlight the importance of enhancing education and promotion that emphasize the convenience and social benefits of online ZIS payments to increase public participation in digital charity.